The relationship between motivation and academic performance among degree students from Faculty of Business Management at UiTM Dungun Terengganu / Noor Suhaida Ariffin - Ariffin, Noor Suhaida (2014)
The purpose of this study was to examine the relationship between motivation which involved McClelland Theory of Needs and student’s academic performance among the degree students from Faculty of Business Management in UiTM Dungun Terengganu. The independent variables involved needs for achievement, needs for affiliation and needs for power while the dependent variable focus on student’s academic performance. A total number of 260 questionnaires were distributed to the respondents and 242 were successfully collected. The data collected then were analyzed by using The Statistical Package for Social Science (SPSS) version 2.0 to obtained the results of the study. The most critical analysis which include Pearson Correlation and Multiple regression analysis were conducted to test the hypotheses which facilitate the findings. The findings revealed that there is a significant relationship between needs for achievement and academic performance and this variable has the most influence on the academic performance. Besides, the other two factor which are needs for affiliation and needs for power also have significant relationship with (p=<0.05). However, needs for affiliation has a very low impact with slight and almost negligible strength of correlation.